Lingkungan Kerja dan Beban Kerja: Pengaruhnya Terhadap Kinerja (Studi Pada Pegawai Bidang Kepegawaian Lembaga Pemasyarakatan Kelas IIA Yogyakarta) - Rahmatia, Reska; Subiyantoro, Ary (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2024)
This research aims to find out how workload and work environment influence employee performance in the staffing sector at the Class IIA Yogyakarta Correctional Institution. Data analysis techniques use validity tests, reliability tests, multiple regression analysis, F tests and t tests. Based on the research results, it was obtained that the multiple regression equation Employee Performance = -.438 + 0.538 Workload + 0.262 Work Environment, shows that there is an influence between workload and work environment on employee performance. From the results of the coefficient of determination test, it shows that the R Square is 0.793. This means that the magnitude of the influence of workload and work environment variables on employee performance in the staffing sector at the Yogyakarta Class IIA Correctional Institution is 79.3%, while the remaining 20.7% must be explained by other causal factors originating from outside this regression method.